Variants Close to NTRK2 Gene Are Associated With Birth Weight in Female Twins. (August 2014) - Metrustry, Sarah J.; Edwards, Mark H.; Medland, Sarah E.; Holloway, John W.; Montgomery, Grant W.; Martin, Nicholas G.; Spector, Tim D.; Cooper, Cyrus; Valdes, Ana M.
<x content-type="archive" xml:space="preserve">Abstract</x> Low weight at birth has previously been shown to be associated with a number of adult diseases such as type 2 diabetes, cardiovascular disease, high blood pressure, and obesity later in life. Genome-wide association studies (GWAS) have been published for singleton-born individuals, but the role of genetic variation in birth weight (BW) in twins has not yet been fully investigated. A GWAS was performed in 4, 593 female study participants with BW data available from the TwinsUK cohort. A genome-wide significant signal was found in chromosome 9, close to the NTRK2 gene (OMIM: 600456). QIMR, an Australian twin cohort (n = 3, 003), and UK-based singleton-birth individuals from the Hertfordshire cohort (n = 2, 997) were used as replication for the top two single nucleotide polymorphism (SNPs) underpinning this signal, rs12340987 and rs7849941. The top SNP, rs12340987, was found to be in the same direction in the Australian twins and in the singleton-born females (fixed effects meta-analysis beta = -0.13, SE = 0.02, and p = 1.48 × 10−8) but not in the singleton-born males tested. These findings provide an important insight into the genetic component of BW in twins who are normally excluded due to their lower BW when compared with singleton births, as well as the difference in BW between twins. The NTRK2 gene identified in this study has previously been associated with obesity.